2022
DOI: 10.1158/0008-5472.can-22-2036
|View full text |Cite
|
Sign up to set email alerts
|

MEX3A Impairs DNA Mismatch Repair Signaling and Mediates Acquired Temozolomide Resistance in Glioblastoma

Abstract: MutS protein homolog 2 (MSH2) is a key element involved in the DNA mismatch repair (MMR) system, which is responsible for recognizing and repairing mispaired bases. Simultaneously, MSH2 identifies DNA adducts induced by temozolomide (TMZ) and triggers apoptosis and autophagy in tumor cells. Previous work has revealed that reduced MSH2 expression is often observed in patients with glioblastoma (GBM) who relapse after chemotherapy. Elucidation of the mechanism behind TMZ-mediated reduction of MSH2 could help imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This further confirmed the correlation between STAT3 level and TMZ resistance. Temozolomide induces DNA methylation of guanine at the O 6 position and triggers the mismatch repair (MMR) system leading to a DNA double strand break that results in cell cycle arrest and apoptosis [27,28]. Nonetheless, in this study another anti-tumor molecular mechanism of TMZ was revealed: preventing cell growth by inhibiting STAT3 signaling.…”
Section: Discussionmentioning
confidence: 78%
“…This further confirmed the correlation between STAT3 level and TMZ resistance. Temozolomide induces DNA methylation of guanine at the O 6 position and triggers the mismatch repair (MMR) system leading to a DNA double strand break that results in cell cycle arrest and apoptosis [27,28]. Nonetheless, in this study another anti-tumor molecular mechanism of TMZ was revealed: preventing cell growth by inhibiting STAT3 signaling.…”
Section: Discussionmentioning
confidence: 78%
“…Including the assessment of MEX3A into prognostic and diagnostic glioma models could enhance their predictive accuracy and provide clinicians with valuable insights into patient outcomes. This aspect is particularly of interest because the recently described involvement of MEX3A in resistance to TMZ [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, under OS, KEAP1 is oxidized, and NRF2 enters the nucleus and binds to the antioxidant response element (ARE) sequence, thereby activating the expression of the abovementioned series of antioxidant enzymes ( 54 58 ). In addition, after DNA damage caused by OS, DNA repair mechanisms in glioma cells are activated to repair damaged DNA and exert indirect antioxidant effects, such as direct repair ( 59 61 ), base excision repair (BER) ( 62 ), mismatch repair (MMR) ( 63 , 64 ), and nucleotide excision repair (NER) ( 65 , 66 ). A summary of the antioxidant defence systems in glioma cells is presented in Table 1 .…”
Section: Ros Production and Antioxidant Defence Systemsmentioning
confidence: 99%